ANALISA PROSES NEWS EDITING DI SITUS BERITA KORAN ONLINE PEWARTA INDONESIA (KOPI) (PENELITIAN PARTISIPATIF PADA DESK REDAKSI KOPI) - Mung Pujanarko Victor Andreas Simanjuntak (Jurnal Citra, 2022)
This research relies on the analysis of the editorial work process of the Indonesian Pewarta Online Newspaper (KOPI) in the process of editing the news that goes to the editorial desk, especially the editorial dashboard. This analysis examines the editorial work process in KOPI online media starting from the process of news traffic in the editorial dashboard in the online media Koran Online Pewarta Indonesia (KOPI), the editing process to the process of adjusting the supporting photos of the news, including captions, as well as picture illustrations, to the process online news content publishing. The outcome of this research is a complete and complete detailed description of the work process for the process of writing and re-writing, editing and publishing news in KOPI online media (Indonesian Pewarta Online Newspaper).